The portrayal of female character in John Steinbeck's The Chrysanthemums: A stylistic analysis - Silalahi, Elisa Debora; Romala, Almira Ghassani Shabrina (Diksi, 2022)
This research presents a stylistic analysis of a short story entitled The Chrysanthemums by John Steinbeck. At the grammatical level, transitivity is employed to achieve the objective of this research. This research is conducted to observe the transitivity process in the short story. By using the transitivity process, this research reveals the portrayal of the main female character. This research applies a qualitative method based on the type of data collected in this research. Based on the findings, there are six types of transitivity processes found, they are material, mental, relational, verbal, existential, and behavioural. Material process portrays the masculine manner of Elisa Allen, Mental process shows the boundaries between Elisa and her husband in their productive outlet, Relational process represents the masculinity in Elisa's appearance, Verbal process represents Elisa as a straightforward person, Existential process expresses Elisa's responsibility in fulfilling her husband's needs, and Behavioral process represents Elisa as a sensitive figure. The dominance of the material process emphasizes Elisa's way of defending herself from an environment that does not value her. Thus, the research findings concluded that Elisa Allen represents a woman who tries to express herself but is often not appreciated in a world dominated by men.Keywords: female character, SFL, stylistics, transitivity